2019
DOI: 10.1016/j.msec.2019.01.112
|View full text |Cite
|
Sign up to set email alerts
|

Biological relevance of CuFeO2 nanoparticles: Antibacterial and anti-inflammatory activity, genotoxicity, DNA and protein interactions

Abstract: Heterometal oxide nanoparticles of bioessential metals are shedding new light to nanoparticleinspired bioapplications. Pairing bioreactive elements like copper and iron can affect the redox dynamic and biological profile of the nanomaterial. Given the complexity of physicochemical properties, biological activity and toxicity concerns, extensive exploration is demanded, especially when active and less active oxidation states participate as in case of cuprous-ferric delafossite CuFeO2 (copper(I)-iron(III)), a le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Another advantage of using nanoparticles is that their antibacterial action can be maintained for an extended period of time with no loss in stability (Cheow and Hadinoto, 2014). Platinum and copper nanoparticles are instrumental in the elimination of resistance plasmids as they interact with the supercoiled plasmid DNA or with topoisomerases involved in replication, transcription, and recombination processes, ultimately leading to elimination of the plasmids (Lakshmi et al, 1988;Lakshmi and Polasa, 1991;Antonoglou et al, 2019). Copper nanoparticles have also been used in plasmid DNA degradation experiments as well as for blocking plasmid conjugation (Chatterjee et al, 2014;Klumper et al, 2017).…”
Section: Chemical Strategies For Removing Mgesmentioning
confidence: 99%
“…Another advantage of using nanoparticles is that their antibacterial action can be maintained for an extended period of time with no loss in stability (Cheow and Hadinoto, 2014). Platinum and copper nanoparticles are instrumental in the elimination of resistance plasmids as they interact with the supercoiled plasmid DNA or with topoisomerases involved in replication, transcription, and recombination processes, ultimately leading to elimination of the plasmids (Lakshmi et al, 1988;Lakshmi and Polasa, 1991;Antonoglou et al, 2019). Copper nanoparticles have also been used in plasmid DNA degradation experiments as well as for blocking plasmid conjugation (Chatterjee et al, 2014;Klumper et al, 2017).…”
Section: Chemical Strategies For Removing Mgesmentioning
confidence: 99%
“…Cu NPs exhibited bactericidal effect against E. coli, S. aureus , and S. mutans , while Ni and Cu–Ni NPs exhibited almost similar effect against the same microorganisms (Argueta-Figueroa et al, 2014 ). In 2019, Antonoglou et al ( 2019 ) reported the antimicrobial performance of Cu–FeO 2 and Cu 2 O NPs, both synthesized by employing the hydrothermal method. The Cu–FeO 2 NPs were found to be small crystalline particles with sizes of around 90–220 nm, while Cu 2 O NPs had a size of around 24.5 nm.…”
Section: Bimetallic Nanoparticle Systems and Their Antimicrobial Propmentioning
confidence: 99%
“…Currently, MONPs of almost 30 different chemical elements are described [5]. Among the most common are alumina [6,7], cerium [8], cobalt [9], copper [10], iron [11,12], gadolinium [13], hafnium [14], magnesium [15], manganese [16], silica, titanium [17], and zinc [18] MONPs.…”
Section: Metal Oxide Nanoparticles: a General Overviewmentioning
confidence: 99%
“…MONPs are of particular interest as they exhibit minor toxicity toward the immune cells and are able to reshape immunity both on local or systemic levels. The immunotherapeutic potential of these NPs for MФ activities and the immune system, in general, is an emerging issue (Table 1) [10,52,53,54].…”
Section: Macrophage Polarization As An Essential Response For Altementioning
confidence: 99%
See 1 more Smart Citation